2010
DOI: 10.1111/j.1552-6569.2009.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraparenchymal Neurocysticercosis in Albuquerque, New Mexico

Abstract: extraparenchymal NCC is more frequent than previously thought. Because clinicians outside the Southwest United States are often unfamiliar with NCC as a cause of chronic meningitis, chronic ventriculitis, or hydrocephalus without obvious cysts, the diagnosis of extraparenchymal NCC often depends on the correct interpretation of neuroimaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…a tumour, cyst or inflammatory swelling). The presence of T solium in the ventricular system may be seen in a 7-30% of patients with NCC [45] and although it has been reported less frequently (6 %) by other authors [46] everything seems to indicate that its frequency is much greater than had been thought previously. [45] Of all forms of presentation of the NCC, the IVNCC is sometimes associated with a fatal prognosis.…”
Section: Neurocysticercosis Intraventricular (Ivncc)mentioning
confidence: 75%
See 1 more Smart Citation
“…a tumour, cyst or inflammatory swelling). The presence of T solium in the ventricular system may be seen in a 7-30% of patients with NCC [45] and although it has been reported less frequently (6 %) by other authors [46] everything seems to indicate that its frequency is much greater than had been thought previously. [45] Of all forms of presentation of the NCC, the IVNCC is sometimes associated with a fatal prognosis.…”
Section: Neurocysticercosis Intraventricular (Ivncc)mentioning
confidence: 75%
“…The presence of T solium in the ventricular system may be seen in a 7-30% of patients with NCC [45] and although it has been reported less frequently (6 %) by other authors [46] everything seems to indicate that its frequency is much greater than had been thought previously. [45] Of all forms of presentation of the NCC, the IVNCC is sometimes associated with a fatal prognosis. The diagnosis of certainty is achieved by methods of neuroimaging, particularly the nuclear magnetic resonance imaging (MRI), which is also indispensable as prior checking to surgery, the choice of treatment and assessment of the response to the same.…”
Section: Neurocysticercosis Intraventricular (Ivncc)mentioning
confidence: 75%
“…This increase likely includes extraparenchymal cases, and a recent study reported an overall frequency of subarachnoid cysts in 2%, ventricular cysts in 6%, and hydrocephalus in 16% of NCC cases (11). These cases represented almost one-third of NCC in a medical center in New Mexico (21). Intraventricular NCC, the presence of Taenia solium cysts in the cerebral ventricular system, occurs in 7-30% of patients with NCC (10;21-23).Thus, extraparenchymal NCC is probably more frequent than previously thought (14;18).…”
Section: Epidemiology Of Extraparenchymal Nccmentioning
confidence: 98%
“…However, this staining of the CSF is not routinely done in most places (8;23). Although the suspicion of NCC as the cause of chronic meningitis is increased when CSF eosinophils are found, CSF eosinophils (above 5%) occur in only 15% of patients (21). It is often a common practice to attribute chronic meningitis and hydrocephalus to tubercular meningitis in the presence of appropriate epidemiologic history and treat empirically by shunting and anti-tubercular therapy.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation